Modeling and efficiency enhancement of SnSe thin film solar cell with a thin CIS layer - Aditya Bhowmik; Ahnaf Tahmid Abir; Md. Alamin Hossain Pappu; Shochin Chandra Das; Bipanko Kumar Mondal; Jaker Hossain (Results in Materials, 2024)
Research has been conducted on a solar cell utilizing Tin Selenide (SnSe) as the absorber material having a structure of n-CdS/p-SnSe/p+-CuInSe2/p++-WSe2 with CuInSe2 (CIS) current augmenting and WSe2 back surface field (BSF) layers. The various parameters in CdS, SnSe, CIS, and WSe2 layers have been adjusted methodically for the optimum output. Under the optimum conditions, the proposed n-CdS/p-SnSe solar cell showcases a power conversion efficiency (PCE) of 26.12 % with VOC = 0.788 V, JSC = 38.62 mA/cm2, and FF = 85.78 %. The PCE of the device enhances to 33.88 % with VOC = 1.09 V, JSC = 38.64 mA/cm2, and FF = 80.24 % owing to the incorporation of the WSe2 BSF layer. However, a conjunction of the CIS layer with the SnSe achieves a higher JSC of 42.54 mA/cm2 and a PCE of 36.45 %. These in-depth simulation findings demonstrate the enormous potential of the SnSe absorber with the CIS current boosting layer for the creation of a thin film solar cell that is both affordable and highly efficient.